Pengaruh Tranining And Development Terhadap Kinerja Karyawan PT Putra Mustika Tour Travel Jakarta - Tio, Lina; Arief, Mustika; Marjohan, Marjohan (Pustaka Galeri Mandiri, 2024)
The purpose of this study is to examine and analyze the effect of the implementation of education and training on the performance of employees of PT Putra Mustika Tour Travel Jakarta. The research method used in this study using a quantitative approach that is intended to test the hypothesis. The data used are primary data obtained through field survey, as for hypothesis testing done by linear regression analysis tool. The object of research is employees of PT Putra Mustika Tour Travel Jakarta with a population of 43 people directly sampled. Sampling technique in this study using saturated sample method. Technique analysis data using simple regression analysis previously tested the validity and reliability. The results obtained sig 0.01 then <0.05 so Ho is rejected so there is influence between the implementation of education and training on employee performance